A synergistic bacterial pool decomposes tebuthiuron in soil - Lima, Edivaldo Wilson de [UNESP]; Brunaldi, Bruno Pinheiro [UNESP]; Frias, Yanca Araujo [UNESP]; Moreira, Bruno Rafael de Almeida [UNESP]; Alves, Lucas da Silva [UNESP]; Lopes, Paulo Renato Matos [UNESP] (Springer Nature, 2022)
This study aimed to propose an eco-compatible strategy to mitigate the possible environmental contamination caused by tebuthiuron. Therefore, we screened potential tebuthiuron-degrading microorganisms from conventional (CS) and no-till (NTS) systems producing sugarcane. Then, they were bioprospected for their ability of decomposing the target-molecule at 2.48 mmol g−1 and 4.96 mmol g−1 into CO2 via respirometry. Integrating microbiota from CS and NTS into an advantageously synergistic bacterial pool produced the highest specific-growth rate of CO2 of 89.60 mg day−1, so outstripped the other inoculum. The bacterial CN-NTS framework notably stabilized the sigmoidal Gompertz curve on microbial degradation earliest and enabled the seeds of Lactucasativa to germinate healthiest throughout ecotoxicological bioassay for cross-validation. Our study is preliminary, but timely to provide knowledge of particular relevance to progress in the field's prominence in remediating terrestrial ecosystems where residual tebuthiuron can persist and contaminate. The analytical insights will act as an opening of solutions to develop high-throughput biotechnological strategies for environmental decontamination.